Consequences of Expected and Observed Victim Resistance for Offender Violence during Robbery Events. (February 2015) - Lindegaard, Marie Rosenkrantz; Bernasco, Wim; Jacques, Scott
Objectives: Drawing on the rational choice perspective, this study aims at explaining why some robberies take place with physical force while others occur only with threat. The focus is how expected and observed victim resistance impact physical force by robbers. Methods: We draw on quantitative and qualitative data obtained from 104 robbers who described 143 robbery events. Based on the coding of behavioral sequences between offenders and victims, we distinguish between the use of physical force at the onset from the use of physical force during the progression of the event. Results: At the onset of robberies, physical force of offenders is influenced by whether they judge the victim to be street credible. During the progression of robberies, offenders are more likely to use physical force against a resistant than against a compliant victim. Conclusions: At the onset of the robbery, offender violence is related to expected victim resistance; during the progression, it is related to observed victim resistance. Future research should focus on behavioral sequences within robbery events including the meaning of victim characteristics and victim behavior in different phases of the event.